2014
DOI: 10.1007/s11605-014-2600-7
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection After Colorectal Surgery: A Rare but Costly Complication

Abstract: Emergent procedures, higher severity of illness, and inflammatory bowel disease are significant risk factors for postoperative CDI in patients undergoing colorectal surgery. Once established, CDI is associated with worse outcomes and higher costs. The poor outcomes of these patients and increased costs highlight the importance of prevention strategies targeting high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
(27 reference statements)
0
17
0
1
Order By: Relevance
“…Patients undergoing colectomy are at a unique risk of Clostridium difficile because of the additional physical disruption of the colonic microflora. The impact of postoperative Clostridium difficile infection is being increasingly reported with overall worse outcome after colon resection [109] . It was reported that postoperative diarrhea or high stoma output regard less of Clostridium difficile infection could increase significantly more superficial surgical site infections including AL [110] , which may indicate the interaction between AL and the intraluminal pressure increased by postoperative diarrhea.…”
Section: Intestinal Microbesmentioning
confidence: 99%
“…Patients undergoing colectomy are at a unique risk of Clostridium difficile because of the additional physical disruption of the colonic microflora. The impact of postoperative Clostridium difficile infection is being increasingly reported with overall worse outcome after colon resection [109] . It was reported that postoperative diarrhea or high stoma output regard less of Clostridium difficile infection could increase significantly more superficial surgical site infections including AL [110] , which may indicate the interaction between AL and the intraluminal pressure increased by postoperative diarrhea.…”
Section: Intestinal Microbesmentioning
confidence: 99%
“…This finding is in contrast with recent literature suggesting that IBD is a risk factor for CDi in the colorectal surgery population. 18 however, corticosteroid use was associated with 50% higher odds of CDi, which may have been a confounder for IBD in previous work in which corticosteroid use was not included as a risk factor in the analysis. furthermore, the current study further confirms that major teaching hospitals and hospitals in urban settings have higher rates of hospital-acquired CDi.…”
Section: Discussionmentioning
confidence: 70%
“…in the surgical population, hospital-acquired CDi is associated with higher rates of complications, intensive care unit admission, 30-day readmission, 30-day mortality, longer length of stay, and up to $14,000 higher costs for the index hospital stay. 6,18,19,21 Because of the high morbidity, mortality, and healthcare use associated with CDi, the association for Professionals in infection Control and epidemiology has published extensive evidence-based guidelines for preventing CDi. 22 the 4 key areas for prevention include hand hygiene, contact/isolation precautions, environmental infection prevention, and antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative complications in colorectal cancer may result in functional impairments or even fatal outcomes for the patient, and also lead to an increase in medical costs associated with an extension of the hospital stay ( 11 13 ). Predicting the development of post-operative complications is useful in the perioperative management of patients, beginning pre-operatively and continuing into the post-operative period, and an early response to post-operative complications has contributed to a decrease in post-operative mortality rates ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%